Mechanisms of ammonium toxicity and tolerance in rice plants - Sousa, Rikaely Torres de (2023)
Excess ammonium in soils causes major problems for plant growth, affecting biomes and agricultural productivity. This problem is aggravated by conditions of low aeration in the soil and excessive nitrogen fertilization, mainly with ammonium sulfate and urea. Ammonium excess or toxicity affects most plant species, but some rice cultivars are tolerant by mechanisms that are not yet fully known. In this work, a rice cultivar tolerant to excess ammonium (Nipponbare) was used as a study model. The thesis is divided into 3 chapters. In the first (chapter I), a “review” on “Ammonium toxicity and tolerance mechanisms in rice plants”, highlighting and updating the state of the art. Chapter II deals with the article “Ammonium overaccumulation in senescent leaves as a novel exclusion mechanism to avoid toxicity in photosynthetically active rice leaves” published in 2021 in the journal “Environomental and Experimental Botany” impact factor 5.7. In this study, an ammonium-tolerant cultivar (Nipponbare) was initially and gradually acclimated to increasing levels of ammonium in the nutrient solution (3.75 and 7.5 mM) and subsequently exposed to elevated levels (15 mM) for 24 days. Plants similarly exposed to the same nitrate levels were taken as controls. We demonstrate a new mechanism of ammonium tolerance through exclusion of its excess by deposition on old, senescent and subsequently dead leaves. This mechanism makes it possible to avoid accumulation of ammonium in mature leaves, preserving their photosynthetic activity. We also demonstrated that excess ammonium strongly reduces the growth of the root system without affecting its cellular integrity, inducing a strong increase in the activity of type III peroxidases. This response suggests that what was previously treated as an ammonium toxicity mechanism (reduced root growth) must be a regulatory mechanism to avoid contact with excess ammonium. In Chapter III (“Spatial changes in N metabolism induced by ammonium toxicity in rice plants”) experiments were conducted in the presence of different ammonium concentrations. The seedlings were initially acclimated in Hoagland & Arnon nutrient solution in decreasing dilutions over the first 3 weeks: 1:4 and 1:2 (NO 3 - /NH 4 + 2.5 mM/0.5 mMin the first week and 5.0 mM/1 mM in the second week) and without dilution (NO3-/NH4+ 10 mM/2mM third week). After this phase, the plants were exposed to 4 treatments for another 14 days: T1 = NH 4 + 2.5 mM (low); T2 = NH 4 + 7.5 mM (moderate); T3 = NH 4 + 15 mM (high) and T4 = control (NO 3 - 15 mM). Treatments with ammonium, regardless of concentration, reduce root growth, but do not affect aerial part growth (stems and total leaves). Gas exchange, photosynthesis and photosystem II activity in expanded and expanding leaves (L7 and L9, respectively) were also not affected by ammonium concentrations (stage V10): basal leaves (L1 – L5), middle leaves (L6 – L8) and top leaves (L9 – L10). Ammonium is intensely accumulated in basal (senescent and dead) leaves, especially at 15 mM compared to the other parties. This accumulation was directly related to the accumulation of some amino acids, especially Gln, Glu, Orn, Pro, Asn, Asp, GABA, Ser and Gly. However, GS, GOGAT and GDH activities were not positively related to either ammonium concentrations or canopy part. Sucrose concentrations were strongly reduced in plants supplied with ammonium, regardless of concentrations. Multivariate analysis (PCA) using the mean content of 40 metabolites (amino acids, organic acids, sugars, among others) indicated that there is a strong grouping of treatments, especially 15 mM NH4+ versus control (15 mM NO3- ). When parts of the canopy were compared within treatments, there was a strong and contrasting grouping between base leaves and top leaves in both the 15 mM NH4+ and control treatments, revealing the strong influence of the physiological stage of leaves on metabolism the plants. The joint analysis of the data reveals that rice has a unique mechanism of acclimatization and tolerance to ammonium toxicity. This mechanism initially involves the induction of early senescence in older leaves which progresses to cell death and apoptosis. During cell death, very high amounts of ammonium are deposited in the leaves, possibly from proteolysis. Apparently, rice leaves and roots exposed to excess ammonium do not trigger increases in total GS, NADH-GOGAT, and amino GDH activities as a mechanism of ammonium detoxification.